Mortality of Kalliapseudes schubartii in unvegetated soft bottoms of the estuarine region of the Lagoa dos Patos - Fonseca,Duane Barros (2006)
Studies were carried iut on seasonal mortality by taking samples of Kalliapseudes schubartii (Crustacea: Tanaidacea) for a year in the estuarine region of the Lagoa dos Patos (southern Brazil). Results demonstrated no significant difference in seasonal mortality rates, which suggest that populations of K. schubartii was heavily preyed on year round and that an assumption of a significantly higher mortality in summer/autumn than in spring/winter might not be held in unvegetated soft bottoms of the estuarine regions of the Lagoa dos Patos.